Maternal thyroid function and the outcome of external cephalic version: a prospective cohort study - van der Donk Riet W; Hasaart Tom H; Kooistra Libbe; Kuppens Simone M; Vader Huib L; Oei Guid S; Pop Victor J (BMC, 2011)
Abstract Background To investigate the relation between maternal thyroid function and the outcome of external cephalic version (ECV) in breech presentation. Methods Prospective cohort study in 141 women (≥ 35 weeks gestation) with a singleton fetus in breech. Blood samples for assessing thyroid function were taken prior to ECV. Main outcome measure was the relation between maternal thyroid function and ECV outcome indicated by post ECV ultrasound. Results ECV success rate was 77/141 (55%), 41/48 (85%) in multipara and 36/93 (39%) in primipara. Women with a failed ECV attempt had significantly higher TSH concentrations than women with a successful ECV (p < 0.001). Multiple logistic regression showed that TSH (OR: 0.52, 95% CI: 0.30-0.90), nulliparity (OR: 0.11, 95% CI: 0.03-0.36), frank breech (OR: 0.30, 95% CI: 0.10-0.93) and placenta anterior (OR: 0.31, 95% CI: 0.11-0.85) were independently related to ECV success. Conclusions Higher TSH levels increase the risk of ECV failure. Trial registration number ClinicalTrials.gov: NCT00516555